Симметризация и начально-краевые задачи для некоторых классов нелинейных параболических уравнений второго порядка - Базалий, Б.В.; Тадеев, А.Ф. (Український математичний журнал, 1993)
Initial boundary-value problems for the differential equations of porous medium and p-Laplace types are considered. By using the Schwan symmetrization method, Lp-estimates for solutions of the initial problems are ob!ained in tcnns of similar estimates for the corresponding symmetric solutions.